Enhanced cytotoxicity of T-DM1 in HER2-low carcinomas via autophagy inhibition - Jinghui Zhang; Xusheng Chang; Yingcheng Bai; Xiancai Ge; Kai Yin; Qun Xin (PLoS ONE, 2025)
Ado-trastuzumab emtansine (T-DM1), a conjugate of trastuzumab and the cytotoxic agent emtansine, has demonstrated significant antitumor efficacy in HER2-positive (HER2+) carcinoma. However, its effectiveness is limited against carcinoma cells with low HER2 expression (HER2-low). Here, we demonstrate that targeting autophagy enhances the cytotoxicity of T-DM1 against HER2-low SGC7901 cells, highlighting the potential of autophagy modulation in improving T-DM1-based therapies for HER2-low carcinomas. Specifically, this study shows that T-DM1 exhibits limited cytotoxic effects on SGC7901 cells, but pharmacological inhibition of autophagy enhances its cytotoxicity. Moreover, transmission electron microscopy revealed that autophagy activation involved the three key phases of autophagic flux: the formation, fusion, and degradation of autophagosomes, while immunoblot analysis confirmed a reduction in Akt/mTOR signaling. Furthermore, autophagy inhibition accelerated the fusion of T-DM1 with lysosomes in SGC7901 cells, as shown by confocal microscopy. Collectively, these findings suggest that while T-DM1 alone induces limited cytotoxicity, combining it with autophagy inhibitors enhances its efficacy against HER2-low carcinoma cells. Mechanistically, autophagy inhibition increases the binding of T-DM1 to lysosomes, potentially facilitating the release of emtansine from the conjugate. These results present a novel strategy that combines T-DM1 with autophagy inhibitors to effectively treat HER2-low gastric cancer, thereby broadening the therapeutic scope of T-DM1 to encompass previously challenging cancer types.